An Empirical Analysis of Bank Capital Adequacy Ratio in Vietnam: A Data Science Approach Using System Generalized Method of Moments - Huy, Nguyen Quoc; Nga, Lu Phi; Tam, Phan Thanh (Journal of Applied Data Sciences, 2024)
Commercial banks and the financial industry face considerable hurdles in light of the fourth Covid-19 outbreak. Commercial banks continuously put capital adequacy measures in place to fulfill Basel regulations. One of the main ways they do this is by issuing bonds, which boost tier 2 capital sources. This helps mobilize capital and assure capital safety for the market's borrowing requirements in the long run. As a result, considering both external and internal variables, this research seeks to investigate what influences the capital adequacy ratio of Vietnam's joint-stock commercial banks. Between 2011 and 2022, the authors combed through data from 25 different Vietnamese joint-stock commercial banks. The authors employed the system generalized method of moments model and other conventional techniques for panel data analysis. The authors derived key findings: Fourteen components are statistically significant at the 1% level, affecting the capital adequacy ratio. Therefore, it is evident that the equity capital of Vietnamese commercial banks has successfully met the required safety standards for assets with credit risk as per legislation. As a result, this assists Vietnamese commercial banks in managing potential losses from credit activities, thus assuring the security of banking operations and protecting depositors. However, the issue suggests policy implications for enhancing Vietnamese commercial banks' future capital adequacy ratio coefficient.